Libraries and the Enlightenment - Bivens-Tatum, Wayne (Library Juice Press, 2012)
"Traces the historical foundations of modern American libraries to the European Enlightenment, showing how the ideas on which library institutions are based go back to the ideas and institutions of that revolutionary time"--Provided by publisher.